Costs of children with medical complexity in Australian public hospitals. (May 2016) - Srivastava, Rajendu; Downie, James; Hall, Jane; Reynolds, Graham
Abstract : Aim: To describe the hospital costs, hospital types and differences across states and territories for children with medical complexity cared for in Australian public hospitals. Methods: Retrospective national administrative database study of 212 Australian public hospitals from six states (excluding Queensland) and two territories that submitted cost data to the National Hospital Costing Data Collection for 2010–2011. Participants included all hospitalised patients with comparisons between adults and children (17 years of age and younger), and adults with chronic diseases and children with medical complexity. Total hospital costs were the main outcome measure. Results: The National Hospital Costing Data Collection contained data from 212 public hospitals; total admissions (adults and children) were 3 519 140 at a total hospital cost of 16 187 400 000. Children accounted for 350 499 (9.9%) of the admissions at a total hospital cost of 1 931 585 123 (11.9%). Of all children, those with medical complexity accounted for 48 758 (13.9%), and their total hospital costs were 620 948 769 (32.1%). Six children's hospitals had 145 213 (41%) of the total children admissions at a total hospital cost of 936 041 843 (48%). Across the states and territories, the number of childhood admissions ranged from 9164 to 146 618 with 4.7–14.8% for children with medical complexity. Total hospital costs ranged from 44 to 592 million with 15.4–39.4% for children with medical complexity. Conclusions: The national burden of hospitalised children is substantial. Children with medical complexity only account for a small percentage of hospitalisations but almost one third of total hospital costs for children, with children's hospitals bearing the major costs.